Esterifikasi Gliserol Sebagai Produk Samping Biodiesel Menjadi Triacetin Dengan Menggunakan Katalis Zeolit Alam Pada Variasi Suhu Reaksi Dan Konsentrasi Katalis - Dedi Meier Silaban; Zuchra Helwani; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Glycerol is by-product of biodiesel. Production of biodiesel will produce glycerol about 10% of total biodiesel. The excess glycerol able to treatment to a more expensive product, such as triacetin. Triacetin is a triester from glycerol and acetic acid. It is used as good additive and also soluble in biodiesel. Triacetin was produced by esterification of glycerol and acetic acid. The aim of this research was to know the influence of the concentration of catalyst and esterification temperature reaction toward glycerol conversion. Esterification of glycerol was done by activated natural zeolite catalyst. The molar ratio of glycerol and acetic acid was 1:7. The temperature that used was 90oC, 100oC, and 110oC, than the concentration of zeolite catalyst was 2%, 4%, and 6% of acetic acid mass. The highest glycerol conversion was 85,21% that reached in reaction temperature 110oC and catalyst concentration 4% of acetic acid mass. The temperature and catalyst concentration of esterification was directly proportional of the glycerol conversion.Key words: Biodiesel, esterification, glycerol, triacetin, zeolite.